UJI BEBERAPA KONSENTRASI EKSTRAK AKAR TUBA (Derris elliptica Benth) UNTUK MENGENDALIKAN HAMA ULAT GRAYAK (Spodoptera frugiperda J. E. Smith) DI LABORATORIUM - Rusli Rustam; Rani Rajani (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2021)
Spodoptera frugiperda J. E. Smith is the main pest attacking maize crops. The usual control is the use of synthetic insecticides, but the continuous or unwise use of synthetic insecticides will have a negative impact on humans and the environment, therefore an alternative insecticide that is safe and environmentally friendly, such as tuba roots (Derris elliptica Benth) is needed. The purpose of this study was to obtain an effective extract concentration of Derris elliptica Benth to control S. frugiperda. The research was conducted at the Plant Pest Laboratory of the Faculty of Agriculture, Riau University, Pekanbaru from February to April 2020. The concentration treatments used were 0 g.l-1 water, 25 g.l-1 water, 50 g.l-1 water, 75 g.l-1 water and 100 g.l-1 water. The experiment used a completely randomized design (CRD) with 5 treatments and 4 replications. The results showed that the concentration of 50 g.l-1 water was able to control the pest of S. frugiperda and could cause total mortality of 80% with an initial time of death of 7,00 hours after application, and LT50 26,00 hours after application